Report on the socioeconomic, humanitarian and human rights situation in the PalmaAfungi-Mocímboa area (Cabo Delgado) - Rufin, Jean-Christophe; Glowacki, Ingrid (Total Energies, 2023)
Patrick Pouyanné, Chairman and CEO of TotalEnergies, entrusted Jean-Christophe Rufin in December 2022, on behalf of the partners of the Mozambique LNG project, with an independent mission to assess the humanitarian situation in the province of Cabo Delgado where the project is located. Jean-Christophe Rufin, a recognized expert in the field humanitarian action and human rights, has carried out several investigation field trips in Mozambique. TotalEnergies publishes his report as well as the action plan decided by Mozambique LNG partners based on the recommendations of the report. The report recalls that the conflict in the province of Cabo Delgado has origins pre-dating the gas development projects and finds its roots in multiple factors not related to Mozambique LNG. It assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. The report assesses the humanitarian operations and the socio-economic development programs undertaken by Mozambique LNG around the Afungi site since 2021. It notes an improved humanitarian situation in the north of Cabo Delgado, in particular with the return of the populations displaced by the conflict to the town of Palma and to a lesser degree to the town of Mocímboa da Praia. The report highlights the execution quality of the actions undertaken by Mozambique LNG and their positive impact on the living conditions of local population. However it recommends the establishment of a dedicated structure with increased resources to further expand these programs and to integrate them into an ambitious and sustainable strategy of local development covering the whole province, and not only guided by the security of the project site. Regarding the populations affected by the development of the Afungi industrial site, Jean-Christophe Rufin recommends several avenues of improvements to finalize in the best conditions the implementation of the resettlement plan and ensure the compensation of affected persons in accordance with the best practices. These improvements relate in particular to the update of the inventories of the affected persons’ assets, the payment timeline of compensations, the provision of agricultural land and the access to fishing areas.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; conflict / conflito; displaced communities / comunidades deslocadas; economic development / desenvolvimento económico; extractive industries / indústrias extractivas; infrastructure - energy / infrastrutura - energia; natural resources - gas / recursos naturais - gás; private sector / setor privado; security / segurança; social action / ação social

Descolonizar os estudos urbanos em África. Conflitos armados e sustentabilidade urbana em Cabo Delgado. - Amaral, Silvia (Desafios para Moçambique 2022, 2022)
Este projecto de investigação pretende, assim, humildemente, contribuir para a descolonização dos estudos urbanos em Moçambique e Portugal, e para a transmutação dos traumas da guerra em oportunidades de desenvolvimento sustentável e prosperidade urbana.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; conflict / conflito; politics / política

Agrarian Change in Northern Mozambique: A ‘New’ Dimension of Research in Light of the Conflict and Violence in Cabo Delgado? - Muianga, Carlos (Instituto de Estudos Sociais e Económicos (IESE), 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Transformação Agrária No Norte De Moçambique: Uma “Nova” Dimensão De Pesquisa À Luz Do Conflito E Violência Em Cabo Delgado? - Muianga, Carlos (Instituto de Estudos Sociais e Económicos (IESE), 2021)
In light of this research context and the different hypotheses that have been put forward, particularly those attributing the conflict to the dynamics of po-verty, social marginalization and the resource extrac-tion dynamics, an argument for a ‘new’ dimension of research in light of the conflict in Cabo Delgado is made. A wide range of information and analysis has been produced, but systematic analysis of broader processes of agrarian change in light of the conflict in Cabo Delgado and their dynamics of change in the northern Mozambique is still scarce, despite referen-ces on the relevance of this being made2. This paper intends to draw attention to the need to understand the political economy of agrarian change in the regi-on. This implies, to use Bernstein's (2010, 1) words, investigating ‘the social relations and dynamics of production and reproduction, of property and power in rural/agrarian societies [in the region] and their historical and contemporary processes of change’.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture - agrarian change / agricultura - transformação agrária; agriculture / agricultura; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Stemming the Insurrection in Mozambique’s Cabo Delgado (International Crisis Group, 2021)
Principal Findings What’s new? Militant attacks and security force operations in Mozambique’s Cabo Delgado province have claimed nearly 3,000 lives, while displacing hundreds of thousands of people. Insecurity has prompted the suspension of a massive gas project. The Islamic State (ISIS) claims ties to the insurrection. Southern African governments are lobbying to send troops. Why did it happen? Mozambican militants have been motivated by grievances against a state that they see as delivering little for them, despite the development of major mineral and hydrocarbon deposits. Tanzanians and other foreigners have joined up, fuelling the insurrection. The country’s historically weak security forces have been unable to stem the onslaught. Why does it matter? Unaddressed, the insurrection could spread further, threatening national stability just as Mozambique is fulfilling a peace deal with the country’s main opposition group and heading into national elections in 2024. It could worsen instability along East Africa’s coast and present ISIS with a new front to exploit. What should be done? Maputo should accept targeted assistance for security operations to contain the insurrection, and avoid a heavy external deployment that could lead to a quagmire. Authorities should deploy aid to build trust with locals and open dialogue with militants. Regional governments should redouble law enforcement efforts to block transnational jihadist involvement.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Conter a Insurreição em Cabo Delgado, Moçambique - International Crisis Group (International Crisis Group, 2021)
O que há de novo? Os ataques de militantes e as operações das forças de segurança na província moçambicana de Cabo Delgado já custaram praticamente 3000 vidas e deslocaram centenas de milhares de pessoas. A insegurança levou à suspensão de um gigantesco projeto de gás. O Estado Islâmico (ISIS) reivindica laços com a insurreição. Os governos do Sul de Africa estão a exercer pressão para o envio de tropas. Porque aconteceu? Os militantes moçambicanos foram motivados pelo descontentamento em relação a um estado que, do seu ponto de vista, pouco fez por eles, apesar do desenvolvimento de depósitos minerais e de hidrocarbonetos significativos. Tanzanianos e outros estrangeiros juntaram-se, alimentando a insurreição. As forças de segurança, historicamente fracas, foram incapazes de conter a ofensiva. Porque importa? Se não for tratada, a insurreição pode vir a alastrar-se, ameaçando a estabilidade nacional enquanto Moçambique está a alcançar um acordo de paz com o principal grupo de oposição do país e antes das eleições nacionais de 2024. A instabilidade ao longo da costa de Africa Oriental poderia piorar e fornecer ao ISIS uma nova frente a explorar. O que deve ser feito? Maputo deveria aceitar uma assistência direcionada para suas operações de segurança, a fim de conter a insurreição, e evitar uma mobilização externa forte, que poderia levar a uma estagnação. As autoridades deveriam fornecer assistência para construir uma relação de confiança com os habitantes locais e um diálogo aberto com os militantes. Os governos regionais deveriam redobrar seus esforços em matéria de aplicação da lei para impedir a implicação jihadista transnacional.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; innovation / inovação

Situação humanitária em Cabo Delgado: milhares de deslocados continuam sem assistência e apoio do Governo e das agências internacionais - Emídio Beula (Centro Para Democracia e Desenvolvimento (CDD), 2021)
Mais de 30.500 pessoas que abandonaram as suas casas devido aos ataques terroristas na vila de Palma em Março último continuam a enfrentar dificuldades de alimentação e de abrigo nos centros de acolhimento. A maioria está no centro de trânsito de Pemba e outros nos campos de deslocados de Metuge. A Matriz de Monitoria de Deslocamentos da Organização Internacional para as Migrações (OIM) continua a registar a chegada diária de deslocados que fogem da insegurança no norte de Cabo Delgado. As autoridades governamentais e as agências humanitárias interromperam, há mais de um mês, as operações de salvamento de pessoas que estão concentradas na vila de reassentamento de Quitunda, a menos de 30 quilómetros da vila de Palma. Devido à insegurança, as agências humanitárias não estão a prestar apoio a milhares de pessoas que estão em Quitunda, nas proximidades do acampamento de Afungi.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

The Role of Women in the Conflict in Cabo Delgado: Understanding Vicious Cycles of Violence - Feijó, João (Observatório do Meio Rural, 2021)
Since October 2017, Cabo Delgado Province has been an arena of armed conflict, translating into destruction and looting, abductions and killings of civilian populations. The conflict intensified throughout 2020, with attacks on district headquarters villages, leading to the forced displacement of hundreds of thousands of individuals. The history of armed conflicts in Mozambique shows that they have had enormous impacts on the civilian population, placed between two opposing groups: rebel forces and government forces. Aware of their respective importance in a guerrilla war (for the possibility of logistical support, camouflage, recruitment, or the provision of information), the warring parties have always related to the civilian population on the basis of mistrust, imposing their domination by force and persuasion, and seeking to interfere in their habitat (in clusters or scattered in the bush). Being physically more fragile, target for sexual predation by armed young men, and traditionally a food producer, women were a recurrent target, remaining in a particularly vulnerable position. In the current armed conflict in northeast Cabo Delgado, there have been numerous reports of abduction of hundreds of young women, and there is much doubt about their whereabouts. However, viewing women only as passive victims of the conflict does not capture the complexity of the situation. Voluntarily or forcibly, by conviction or without choice, the literature shows that women play an active role in armed conflicts, as observers and providers of military information, in providing logistical support, as vigilantes, and even as soldiers. This active involvement of women is all the more evident the larger the social support base of the insurgent groups. This study aims to portray the impact of the armed conflict on women during the armed conflict in northern Cabo Delgado, analyzing not only the wide range of violence committed against them, but also the forms of collaboration (more or less voluntary) with rebel groups and their organizational dynamics.
ISBN: 978-2-490093-28-1
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; gender / género; ⛔ No DOI found

Observatory of Illicit Economies in Eastern and Southern Africa (Global Initiative Against Transnational and Organized Crime, 2021)
Illicit flows are a major part of the political and economic landscape of northern Mozambique. In South Africa, the trade in poached abalone and the trafficking of synthetic drug still remain joined today. The impact that heroin capsules have had in Durban in terms of violence, profitability and local demand for heroin. How illicit gold from South Sudan and the Democratic Republic of Congo flows through Uganda
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; conflict / conflito

Bispo de Pemba critica Nyusi: "Se eu fosse presidente, a minha presença seria outra. Estaria a falar de Cabo Delgado todos os dias" - Castro, Pedro Jorge (Moçambique para todos, 2021)
"Como é que um corrupto pode lutar contra si mesmo? É preciso uma espécie de revolução." As ameaças do governo. A guerra. E o deslocado que disparou contra insurgentes. Entrevista ao Bispo de Pemba.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - Pemba; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 26 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montepuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 26 April 2021, an estimated number of 1,118 IDPs were registered in the four districts bringing the total number of IDPs to 27,913 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Cabo Ligado 45 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Following the rise of Islamist group al-Shabab in Cabo Delgado - Marie Toulemonde (The Africa Report.com, 2021)
A visual explanation of how Mozambique’s islamist group al-Shabab has grown over the years in the northern Cabo Delgado province.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; extractive industries / indústrias extractivas

An overview of foreign security involvement in Mozambique (defenceWeb, 2021)
A number of private security companies, foreign governments and militaries have become involved in Mozambique in its fight against the insurgency in Cabo Delgado, but the Mozambican government has so far largely limited external involvement. Nevertheless, there are a number of companies and countries providing security and security assistance to Mozambique. Private military contractors Russian […]
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Cabo Ligado 44 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

‘Some hid in the sea’: Islamist attack on Mozambique town a turning point in Africa’s ignored war - Cotterill, Joseph (Financial Times, 2021)
French group Total suspends work at gas plant near Palma despite authorities’ claims order has been restored
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Hunger spreading as Mozambique crisis reaches tipping point - Marima, Tendai (AlJezeera, 2021)
Thousands of people shelter in displacement camps with limited food supplies across Cabo Delgado following Palma attack.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Caracterização e Organização Social Dos Machababos a Partir dos Discursos de Mulheres Raptadas - Feijó, João (Observatório do Meio Rural, 2021)
A intensificação do conflito militar no Norte de Cabo Delgado despertou a atenção de jornalistas, investigadores, analistas de segurança e diplomatas. O facto de os rebeldes armados não darem entrevistas a jornalistas e investigadores resulta num grande desconhecimento sobre as suas dinâmicas internas nas zonas ocupadas, pelo que o mundo dos insurgentes constitui um território repleto de mistérios. Por outro lado, o rapto de centenas de jovens mulheres gera interrogações em torno do respectivo paradeiro, originando inquietação social. O pouco conhecimento existente acerca das formas de organização interna dos insurgentes resulta de testemunhos oculares de quem privou com o grupo, nomeadamente desertores ou mulheres que estiveram em cativeiro. A partir de 23 entrevistas a mulheres vítimas de agressão ou sequestro por grupos insurgentes foi possível concluir que os membros do grupo têm origens e percursos sociogeográficos heterogéneos, sendo a maioria oriunda do litoral Norte de Cabo Delgado, com registos de indivíduos provenientes do planalto de Mueda, do litoral de Nampula, assim como um crescente número de estrangeiros, provenientes da costa oriental africana e de países árabes. Os insurgentes dispõem de diferentes bases, instaladas em aldeias abandonadas por civis ou nas matas.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Characterization and Social Organization of Machababos from the Discourses of Kidnapped Women - Feijó, João (Observatório do Meio Rural, 2021)
The intensification of the military conflict in Northern Cabo Delgado has attracted the attention of journalists, investigators, security analysts and diplomats. The fact that armed rebels do not give interviews to journalists and researchers results in a great ignorance about their internal dynamics in the occupied areas, and so the world of insurgents is a territory full of mysteries. On the other hand, the abduction of hundreds of young women raises questions about their whereabouts, causing social unrest. The little knowledge of the insurgents' forms of internal organization stems from eyewitness testimonies of those who lived with the group, including defectors or women who have been in captivity.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Displacement Tracking Matrix - Mozambique Ett Report: No. 54/ 27 March - 15 April 2021 17:00h Emergency tracking tool (ett) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 15 April 2021, an estimated number of 1,260 IDPs were registered in the four districts bringing the total number of IDPs to 19,921 people who have been displaced from Palma. IDPs continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Hundreds Missing After Mozambique Attack (Human Rights Watch, 2021)
Hundreds of people remain missing five days after an Islamic State (ISIS)-linked armed group known as Al-Shabab raided the town of Palma in Mozambique’s northern Cabo Delgado province, killing and wounding an unknown number of civilians and causing thousands to flee.
Keywords: #Reporting & Media / Reportagem & Mídia; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; security / segurança

Cabo Ligado 43 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

As Militants Seize Mozambique Gas Hub, a Dash for Safety Turns Deadly - Goldbaum, Christina; Schmitt, Eric; Walsh, Declan (The New York Times, 2021)
An agonizing choice for nearly 200 people holed up in a hotel as gunmen roamed unchecked: Wait overnight for rescue? Or make a run for it?
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Mozambique: Firing in Palma near Total's LNG project, population fleeing - Lusa (Mozambique, 2021)
The town of Palma, in Cabo Delgado, was under gunfire on Wednesday afternoon and the population is fleeing, different sources who were in communication with the headquarters of the district that hosts the gas projects in northern Mozambique told Lusa. Machine gunfire was heard in the town and the
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; extractive industries / indústrias extractivas; private sector / setor privado

Cabo Ligado 42 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Social protection during conflict: reflections on Tigray - Sabates-Wheeler, Rachel; Lind, Jeremy (Institute of Development Studies, 2021)
Conflict and an ensuing humanitarian crisis in Ethiopia’s northern Tigray region have led to substantial population displacement and threaten the lives and livelihoods of millions. In a situation where rising needs outstripped preliminary humanitarian responses and where safety net programmes that were purposed for shock-response have been curtailed or stopped functioning altogether, what are the […]
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social

Cabo Ligado 41 - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

State Department Terrorist Designations of ISIS Affiliates and Leaders in the Democratic Republic of the Congo and Mozambique (United States Department of State, 2021)
The Department of State has designated the Islamic State of Iraq and Syria – Democratic Republic of the Congo (ISIS-DRC) and the Islamic State of Iraq and Syria – Mozambique (ISIS-Mozambique) as Foreign Terrorist Organizations under section 219 of the Immigration and Nationality Act, as amended. The Department has also designated ISIS-DRC and ISIS-Mozambique as […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

US hits IS groups in Mozambique, Congo with terror sanctions (AP NEWS, 2021)
WASHINGTON (AP) — The Biden administration on Wednesday designated two Islamic State affiliates in Mozambique and the Democratic Republic of Congo as “foreign terrorist organizations,” imposing...
Section: World News
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

A Insurgência Jihadi em Moçambique: Origens, Natureza e Início - Morier-Genoud, Eric (Instituto de Estudos Sociais e Económicos (IESE), 2021)
Resultante de uma investigação com trabalho de campo em Cabo Delgado em 2018 e 2019, este novo Cadernos IESE nº 21, da autoria de Eric Morier-Genoud, explica a origem, natureza, e dinâmica da guerra no norte de Moçambique com base numa análise da historicidade e das dinâmicas internas das sociedades locais. Defende o argumento segundo o qual é mais produtivo pensar nos insurgentes do Al-Shabaab em termos da sua trajectória histórica, evoluindo de uma seita islâmista para um grupo armado jihadi violento, passando actualmente por um processo de internacionalização que poderá se evoluir de várias formas no futuro.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado (Mozambique Conflict Observatory ) Cabo Ligado Weekly: 1-7 March - ACLED (ACLED, 2021)
Insurgents struck throughout Nangade district last week, nearly isolating Nangade town in a series of attacks. On 1 March, insurgents began setting roadblocks on the R763 south of Nangade town, cutting off the main route between Nangade and Mueda. The same day, insurgents killed two farmers working near the village of Eduardo Mondlane, just east of Litingina. On 2 March, more insurgent roadblocks sprang up near Muiha village, in the northwest of Nangade district, near where the borders separating Nangade, Mueda, and Tanzania meet. Insurgents were also seen the same day in the countryside just west of Muiha, where they chased farmers from their fields. No casualties were reported. The incursions west of Muiha are the farthest west incidents in Cabo Delgado involving insurgent fighters ACLED has yet recorded. Far to the east, insurgents once again attacked the border post of Namoto, Palma district on the night of 2 March. Despite a military unit being deployed to protect the area after it was attacked on 27 February, insurgents were able to loot the area and burn the border post to the ground. Helicopters evacuated border police shortly after the attack began, and no casualties have been reported. The next day, insurgents used their roadblock system to ambush a military vehicle traveling on the R763 from Nangade town to Mueda. The ambush took place near Litingina, about 10 kilometers south of Nangade town. Insurgents placed logs in the road and opened fire on the vehicle as it approached. The soldiers in the vehicle returned fire with a rocket propelled grenade and barreled through the roadblock, but not before three soldiers had been killed. The deceased include a lieutenant colonel and two enlisted men. The same day, insurgents killed two civilians from the same family in the village of N’gangolo, which sits on the R763 south of Litingina. That night, insurgents raided the village of Samora Machel, east of Litingina. No details of that attack have been reported. Insurgents drew even closer to Nangade town on 4 March when they attacked the village of 3 de Fevereiro, 9 kilometers east of the district capital. Most civilians had fled to Nangade town before the attack, but they could see the smoke from 3 de Fevereiro as insurgents burned homes in the village. Insurgents also returned to Samora Machel that night, but, again, no details of the attack emerged. A report by Pinnacle News, confirmed by a Cabo Ligado source, notes that insurgents sent messages to Palma civilians, threatening to attack the town on 5 March. As with past threats of specific attack dates, no actual attack on Palma came on 5 March, although more security forces were deployed to the town as a precaution. On 6 March, government forces attacked an insurgent encampment at Nkonga, in eastern Nangade district near the border with Mocimboa da Praia. The village had been deserted following insurgent attacks in the area, and insurgents had commandeered it as a place to hold hostages and stockpile looted goods. Supported by five helicopters, government troops assaulted the village and killed and captured multiple insurgents. Goods looted from Nangade district were recovered, and hostages taken by insurgents during their Nangade raids were freed
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

Afinal, não é só Cabo Delgado! Dinâmicas da insurgência em Nampula e Niassa - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2021)
Nos últimos três anos e meio, Moçambique enfrenta uma violência armada desencadeada por um grupo de natureza jihadista. Com origens na zona norte de Cabo Delgado e localmente conhecido pela designação Al-Shabaab, o grupo surgiu como uma seita religiosa (Morier-Genoud, 2020) e, de seguida, constituiu-se numa unidade militarizada, tendo partido para a violência armada a 5 de Outubro de 2017. Baseado em trabalho de campo nas províncias de Cabo Delgado, Nampula e Niassa, este texto procura analisar a insurgência com base em dinâmicas de alguns distritos de Nampula e Niassa. Com enfoque nos factores do avanço da insurgência no terreno, o texto sublinha o argumento, segundo o qual, a compreensão do desenvolvimento da insurgência em Cabo Delgado passa, entre outros aspectos, pela análise das dinâmicas sociais, económicas e religiosas das províncias vizinhas, nomeadamente Nampula e Niassa, que se transformaram em espaços férteis de recrutamento, particularmente a partir de 2018. O argumento é desenvolvido em dois momentos. No primeiro momento, o texto procura identificar e analisar os principais factores que conduziram ao alastramento da insurgência para mais distritos de Cabo Delgado e à tentativa de instalação de células de tendência radical em alguns distritos de Nampula e Niassa. No segundo momento, focaliza-se a atenção para as dinâmicas de recrutamento a nível interno, com destaque para alguns distritos localizados na zona costeira de Nampula e na fronteira entre a província de Niassa e a Tanzânia.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Conflict is the new ‘hazard’ on the social protection block - Sabates-Wheeler, Rachel; Slater, Rachel; Lind, Jeremy; Harvey, Paul; Oosterhoff, Pauline; Faith, Becky; Naess, Lars Otto; Selby, Jan; Roberts, Tony; Longhurst, Daniel; Rohwerder, Brigitte; Collyer, Michael; et al. (Institute of Development Studies, 2021)
Although social protection has the potential to address crises in different ways, the evidence base is thematically and geographically patchy. The Foreign, Commonwealth and Development Office-funded (FCDO)-funded Better Assistance in Crises (BASIC) Research programme aims to inform policy and programming on effective social assistance in situations of crisis, including those experiencing climate-related shocks and stressors, protracted conflict and forced displacement.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; Social Protection PEA; conflict / conflito; social protection / proteção social

Mozambique: ExxonMobil again postpones final decision on Rovuma LNG (Mozambique, 2021)
US oil company Exxon has postponed for the third consecutive year the Final Investment Decision on the natural gas exploration project in Mozambique, putting the $30 billion investment in doubt. According to Bloomberg news agency, which quotes the company's Senior Vice President Neil Chapman, Nei
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; private sector / setor privado

O que vi foi a morte: crimes de guerra no "cabo esqueçido" de Moçambique (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

What I saw is death: War crimes in Mozambique's forgotten cape (Amnesty International, 2021)
After suffering decades of under-investment, government negligence, and crushing poverty, the province of Cabo Delgado, the poorest in Mozambique, is now the site of a raging insurgency. Over 1,300 civilians have been killed; another 500,000 have been displaced, and towns and villages have been left in ruins. Fighting has intensified since an armed group locally known as Al-Shabaab attacked the northern port town of Mocímboa da Praia in October 2017. In a series of attacks, Al-Shabaab has killed civilians and burned their homes; the security forces of Mozambique have abused the very people they are meant to protect, and the Dyck Advisory Group, the private military company hired as a quick reaction force, has fired machine guns and dropped grenades indiscriminately from their helicopters. The people of Cabo Delgado are caught between three forces, and the result is a massive humanitarian crisis.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Mozambique: Civilians killed as war crimes committed by armed group, government forces, and private military contractors – new report (2021)
The new report documents serious violations of international humanitarian law by all parties to the conflict in Cabo Delgado.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Cabo Ligado Monthly: March 2021 - ACLED (ACLED, 2021)
In This Report: Analysis of the IS claim of the Palma attack in the context of the overall relationship between IS and the Cabo Delgado insurgency Discussion of growing tensions between displaced people, host communities, and aid organizations in districts with growing displaced populations Update on international involvement in the Cabo Delgado conflict and analysis of the role that South African companies Dyck Advisory Group and Paramount Group play in the conflict
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Cabo Ligado 39 - ACLED (ACLED, 2021)
On 22 February, insurgents conducted two attacks along the border between Nangade and Mocimboa da Praia districts. The first, a morning attack, took place at Ingalonga, Nangade district. Insurgents beheaded two people there. Later that day, across the border in Mitope, Mocimboa da Praia district, insurgents captured three women and three men who had been working in their fields. One woman was released, and the three men were beheaded. Local militias deployed to the area in response, but no clashes were reported. Three days later insurgents struck closer to the Nangade district capital, attacking the village of Luneque, which is only 10 kilometers from Nangade town. The attackers killed four civilians in the town, and caused many others to flee to the district capital. On the evening of 26 February, insurgents surprised residents of Quirinde, Palma district as they ate dinner. Residents fled, but insurgents killed seven, three of whom were beheaded. Insurgents also destroyed homes and looted food and other goods. Quirinde is a coastal village north of Palma town, about six kilometers east of Quionga, which insurgents attacked on 19 February. One source reports that helicopters belonging to government forces or government contractors pursued the Quirinde attackers, causing an indeterminate number of casualties. According to Pinnacle News, the government has deployed two battalions of the police Rapid Intervention Unit to the area in an attempt to prevent further insurgent attacks on the route between Palma and the Tanzanian border.
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Ten Conflicts to Worry About in 2021 (ACLED, 2021)
A review of key developments in 2020 with a look toward trends to watch in the coming year.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Multinational enterprises, political institutions, and violence: a case study from Mozambique - Mairoce, Carlos; Silberberger, Magdalene; Zweynert, Joachim (Journal of Institutional Economics, 2021)
Based on the concept of limited and open access orders (LAO/OAO), this paper explains what appears to be a paradox: how was it possible that a former civil war country, Mozambique, which had been extremely successful in attracting foreign direct investment (FDI) and which the International Monetary Fund praised as a great Sub-Sahara African success story in 2007, only a few years later found itself on the brink of a new civil war? We argue that the destabilization of the country was the result of a toxic mix of domestic politics and a massive inflow of FDI. FDI provided rents to an increasingly dominant state party, FRELIMO, which could be appropriated one-sidedly. It then used these rents to oppress RENAMO, its previous civil war enemy and currently its main opposition party, to monopolize power. This strategy seemed to be successful until RENAMO, faced with the risk of being politically marginalized (and of losing its rents accordingly), returned to armed conflict in 2013. By analyzing the links between the macro-level of national politics and the micro-level of an enterprise and by embedding the interplay between polity and economy into an international context, the paper also makes a theoretical contribution to the LAO/OAO concept.
Publisher: Cambridge University Press
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; L - english / inglês; conflict - civil war / conflito - guerra civil; extractive industries / indústrias extractivas; private sector / setor privado

Mozambique - Emergency Tracking Tool - Palma Crisis Report - 50 (27 March - 10 April 2021) - IOM - International Organisation for Migration (IOM, 2021)
Following the recent attacks in Palma Sede, DTM teams in Nangade, Mueda, Montpuez, and Pemba districts continue to register significant rise in IDP arrivals since 27 March. On 10 April 2021, an estimated number of 603 were registered in the four districts bringing the total number of IDPs to 15,179 People who have been displaced from Palma continue to arrive in Nangade on foot and by bus from Nangade to Mueda, Montepuez, and Pemba.
Keywords: G - Mozambique / Moçambique; G - north / norte; GD - Palma; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

UNHCR Mozambique IDP Response External Update 2-15 April.pdf - UNHCR (UNHCR - The UN Refugee Agency, 2021)
As of 15 April, over 20,0001 people from Palma are forcibly displaced, in the aftermath of Non-State Armed Group (NSAG) attacks on 24 March. They fled to the districts of Nangade, Mueda, Montepuez and Pemba by land, foot, air and sea. This is in addition to the nearly 700,000 already displaced in the provinces of Cabo Delgado, Nampula, Niassa, Sofala and Zambezia as a result of violence and insecurity in Cabo Delgado. UNHCR received reports that several families from Palma attempted to seek asylum in Tanzania due to the proximity to the border and were forcibly returned to Mozambique.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; accountability / responsabilização; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; displaced communities / comunidades deslocadas

Humanitarian Response Plan Mozambique (United Nations Office for the Coordination of Humanitarian Affairs (OCHA), 2020)
OCHA Humanitarian Response Plan for Northern Mozambique Conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict / conflito; displaced communities / comunidades deslocadas

Gender and countering violent extremism (CVE) in the Kenya- Mozambique region - Idris, Iffat (Institute of Development Studies, 2020)
This evidence synthesis drew on a mixture of academic and grey literature. While the literature on Kenyan women and Al-Shabaab was quite extensive (albeit with gaps, e.g. on returnees), nothing was found on women and Ansar al-Sunnah/violent extremist groups operating in northeastern Mozambique and the Mozambique-Tanzania cross-border region. This report should be read in conjunction with two earlier reviews of gender and CVE (Idris & Abdelaziz, 2017; Idris, 2019). This report builds on those – focusing on the literature on gender and CVE published since then, and on recent guidance on CVE programming – rather than reproducing their findings. This report covers three main themes: the role of women in violent extremism and in CVE (drawing on global evidence); Kenyan women’s involvement in Al-Shabaab and approaches to CVE and gender in that country; and recommendations/guidance for gender and CVE programming.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; gender / género

Niassa: MASC desencoraja envolvimento de jovens nos ataques terroristas - User, Super (2020)
A Fundação MASC - Mecanismo de Apoio a Sociedade Civil, no Niassa, desencoraja o envolvimento de jovens nos ataques terroristas na vizinha província d...
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Niassa; L - portuguese / português; civil society / sociedade civil; conflict / conflito; youth / juventude

The Relationship Between Population Growth, Age Structure, Conflict, and Governance in Sub- Saharan Africa - O’Driscoll, Dylan (Institute of Development Studies, Brighton, UK, 2020)
This report addresses the relationship between population growth, age structure, and conflict in Sub-Saharan Africa (SSA). The literature reviewed for this report presents strong evidence that age structure and population growth matter for conflict. There is particularly strong evidence that points to the relationship between young age structure and conflict, although studies that disaggregate types of conflict and characteristics of young age structures (urban, male, etc.) tend to offer more robust findings. Youth bulges in particular have been associated with increased risk of conflict. The general consensus is that, in countries that will continue to experience high rates of population growth and large youth cohorts, the potential for conflict will continue to be elevated. COVID-19 is putting a dent in already weak formal employment and education. Policy responses to the pandemic will have lasting impacts for those most affected, including young people, and should therefore include them in response. The following policy recommendations are made in the literature including Patriarchal gender norms and masculinity contribute to violence and conflict, and thus policies aimed at increasing gender equality help mitigate conflict risk; The prediction that youth bulge is associated with the onset of conflict should encourage policymakers in countries with young age structures to address societal and economic inequality and foster greater inclusion of the younger cohorts into society; and Youth underemployment (and unemployment) remain an issue in SSA; bringing about structural changes that facilitate the transition into the labor market is likely to mitigate the conflict risks associated with youth bulges
Accepted: 2020-11-04T11:13:17Z Publisher: Institute of Development Studies
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; conflict / conflito; gender / género; youth / juventude

Narrativas Alternativas: Lançamento Do Álbum Moçambique Yethu! #stopviolenciaextremista - MASC, Fundação (Fundação MASC, 2020)
Desde o final de 2017, Cabo Delgado, tem sido palco de violentos ataques de grupos […]
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; civil society / sociedade civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

Broadening the Analysis of Peace in Mozambique: Exploring Emerging Violence in Times of Transnational Extractivism in Cabo Delgado - Alberdi, Jokin; Barroso, Manuel (Global Society, 2020)
This article explores the contemporary expressions of violence and oppression linked to the action of the extractive industry in the northern province of Cabo Delgado, Mozambique. Twenty-five years after the signing of the General Peace Agreement, the debate on peace in the country has remained confined to the resurgence of armed clashes between RENAMO combatants and State security forces in recent years. It is proposed here, however, that the current range of violence that challenge peace in Mozambique is broader and more diverse, requiring an analysis that considers the arrival of transnational extractivism. This study, taking Cabo Delgado province as a case-study, aims to broaden the scope of academic debates by establishing a dialogue with the practice of local peacebuilding, and contributions from the critical political economy of development and the collective capability approach.
Publisher: Routledge _eprint: https://doi.org/10.1080/13600826.2020.1772730
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; extractive industries / indústrias extractivas

The Mozambique Conflict and Deteriorating Security Situation - Bukarti, Bulama; Munasinghe, Sandun (Tony Blair Institute for Global Change, 2020)
For almost three years, the ISIS-affiliated extremist group Ansar al-Sunna has spearheaded an insurgency in Mozambique’s northern province of Cabo Delgado. In recent months the situation in Cabo Delgado has deteriorated significantly and violent attacks are now frequent. Militants have begun to target military positions having previously focused on civilian targets. It is a sign that the group is growing in resilience, operational capacity and confidence. From its first few attacks in Mocimboa de Praia in late 2017, the group now launches more than 20 attacks every month in an insurgency that covers nine major towns and districts along the Cabo Delgado coast. A battle for the town of Macomia at the end of May demonstrates the group’s organisational capacity and ambition as well as an escalation in the government’s counter-offensive efforts. On 30 May 2020, government forces engaged Ansar al-Sunna militants in one of the largest counter-terrorism operations to date, resulting in the reported deaths of 78 insurgents, including two of the group’s leaders. The extent to which this will impact Ansar al-Sunna’s operations and long-term ambitions remains to be understood.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; youth / juventude

The Islamic State and the crises of COVID 19 - Victoria, Artur (2020)
According to the Homeland Security Today website, the statement lists "guidelines for dealing with the epidemic". For the Islamic State, the main advice is "to trust God and take refuge in Him from disease", but followers have an "obligation" to take protective measures to prevent it. Among these measures, the terrorist group emphasizes that "the healthy should not enter the land of the epidemic and the sick must not leave it". According to the council, terrorists should not travel to Europe and the United States, which are common targets in the West, nor to countries in the Middle East such as Iran, Iraq and Saudi Arabia. The group dominates provinces and has active cells in some countries still free of the disease, such as the Central and West Africa region, as well as Syria and Yemen, where civil war makes it difficult to collect information about epidemics. But cases have already been confirmed in Algeria, Egypt, Iraq, Afghanistan, India, the Philippines and Indonesia. The reorganization in Africa of ISIS - Evolution and progression in Mozambique In Mozambique, according to statements by the President of the Republic and the Minister of Defence, there are groups of terrorists in the district of Cabo Delgado and other groups in the centre, but who are considered to be affected by RENAMO. The situation is complicated because as these groups demonstrate, they show all the characteristics of IS members.
Keywords: #Reviews & Framing / Revisões e Organização; G - Rest of the World / Resto do Mundo; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Face ao conflito no norte, o que Moçambique pode aprender da sua própria guerra civil (1976 – 1992)?: Uma análise das dinâmicas da insurgência em Cabo Delgado - Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Analisa as dinâmicas da insurgência em Cabo Delgado e procura interrogar o que Moçambique pode aprender dos seus ciclos de violência armada, particularmente a guerra civil, para fazer face ao actual conflito no Norte do país.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

War in resource-rich northern Mozambique – six scenarios 2020.pdf - Santos, F. A. dos (Chr. Michelsen Institute, 2020)
Since the October 2017 attacks by alleged Islamist insurgents, commonly referred to as Ahlu Sunnah Wa-Jama and locally know as Al Shabab, on Mocimboa da Praia, it has not been entirely clear who the attackers were, what their strategic objectives are and on whose domestic and international support they rely. This paper, grounded in a historical understanding of conflict in northern Mozambique’s Cabo Delgado Province, seeks to identify possible stakeholders and scenarios in what we no longer see as an insurgency, but a war.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; natural resources - gas / recursos naturais - gás; natural resources / recursos naturais

Desenvolvimento socioeconómico de Cabo Delgado num contexto de conflito - João Feijó; António Souto; Jerry Maquenzi (Observador Rural, 2020)
Um conjunto de contradições internas e de longa duração estruturam as relações socioeconómicas na província, estando em grande medida na origem da conflitualidade actual. Não obstante a crescente interferência de factores externos na dinamização do conflito, os dados disponíveis permitem-nos concluir que, enquanto persistirem elementos internos de contradição, não será possível encontrar uma solução sustentável para o conflito. Não obstante o conflito implicar, inevitavelmente, uma intervenção militar, para prover a segurança das populações e de bens, as profundas contradições internas existentes obrigam à realização de um plano de desenvolvimento social e económico, entendido como a melhor estratégia de contra-insurgência, limitando o alastramento do conflito armado por outras zonas da província marcadas pela pobreza e por históricas relações de protesto em relação ao Estado. Uma vez que as informações são escassas e imprecisas e a situação militar no terreno é bastante imprevisível, torna-se difícil definir linhas gerais para um plano de intervenção. Não obstante, neste documento pretende-se apresentar um conjunto de elementos que devem ser considerados, de forma coerente, na implementação de qualquer projecto de desenvolvimento, distinguindo as diferentes áreas socioeconómicas de intervenção na província de Cabo Delgado, em função da realidade actual.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict / conflito; economic development / desenvolvimento económico

Protecção social em contexto de terrorismo: que implicações tem a insurgência islâmica nos mecanismos formais de protecção social em Moçambique? - Siúta, Moisés (2020)
O impacto do terrorismo em Moçambique é uma realidade que não se restringe apenas à zona Norte do país. O IDeIAS nº 137, da autoria de Moisés Siúta, procura discutir as suas implicações nos sistemas formais de protecção social tendo em conta o desafio que enfrentam de garantir protecção e bem-estar social da população nas regiões mais afectadas sem, no entanto, deixar para trás a população vulnerável a diversos riscos como seca, cheias e a pandemia.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito; social protection / proteção social; ⛔ No DOI found

Geografia Eleitoral e Insurgência em Cabo Delgado - Brito, Luís de (Desafios para Moçambique, 2020)
This chapter looks at the origins of the extremist insurgency in Cabo Delgado and posists that to understand its origins, we must look beyond religious extremeism and to other factors in order to analyse the situation from difference perspectives. This study looked at electoral data in Cabo Delgado to determine if there is a relationship bwtween voting patterns, including abstention, and political cleavages and social conflict.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; Northern PEA; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; electoral geography / geografia eleitoral

Ugandenses e Tanzanianos do Al-Shabaab: um olhar à dimensão internacional do conflito em Cabo Delgado - Chichava, Sergio (Desafios para Moçambique, 2020)
O conflito militar que, desde 5 de Outubro de 2017, se abate sobre Moçambique, com particular incidência na província de Cabo Delgado e protagonizado por um grupo localmente conhecido por Al-Shabaab, cuja pretensão é substituir o Estado laico por um Estado regido pela Sharia, tem sido regularmente descrito pelas autoridades moçambicanas como tendo, além de uma dimensão interna, uma componente externa. Desde o início do conflito, as autoridades locais falam da prisão ou da procura de vários estrangeiros que estariam a treinar, financiar e dirigir a «insurgência» em Cabo Delgado com vista a retardar o desenvolvimento do País e a explorar ilegalmente diversos recursos naturais. De entre os diversos estrangeiros frequentemente mencionados, o destaque vai para tanzanianos e ugandenses. Por seu turno, o Al-Shabaab tem vindo a reclamar uma dimensão internacional, declarando fidelidade ao Estado Islâmico (EI) ou Daesh. Ao que tudo indica, o Daesh também reconhece o Al-Shabaab, que designa por «soldados do Califado» pertencentes ao Estado Islâmico da Província da África Central (ISCAP, no acrónimo inglês), uma região cujos contornos geográficos ainda não estão bem claros, mas que englobaria actualmente, além Moçambique, a República Democrática do Congo (RDC), País onde está baseado o grupo islamista ugandês Forças Democráticas Aliadas (ADF), que também tem sido apresentado nalguns fóruns como tendo relações com o Al Shabaab em Moçambique, através da presença de alguns dos seus militantes neste País, ou através do recrutamento e treino de jovens moçambicanos na RDC. Com base nos elementos acima, o objectivo deste texto é fazer uma breve análise da componente internacional do AlShabaab, olhando para a sua ligação com a Tanzânia, o Uganda e o EI. Mais precisamente, olhando para o perfil dos cidadãos ugandeses e tanzanianos que têm sido referenciados como sendo do Al-Shabaab, o texto procura responder às seguintes questões: quem são os tanzanianos e ugandeses do Al-Shabaab? Como chegaram a Moçambique? O que pretendem? Porque escolheram a província de Cabo Delgado? Será o Al-Shabaab uma filial do Estado Islâmico? Para responder a estas questões, primeiro apresenta-se o perfil dos tanzanianos e ugandeses do Al-Shabaab; a seguir, apresentam-se algumas hipóteses sobre as suas pretensões; e, por último, abordam-se alguns elementos sobre a possível ligação do Al-Shabaab ao Daesh ou ao EI.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Estudo de caso: Cabo Delgado (Moçambique). A terra onde não se come o que se produz e produz o que não se come - Cunha, Teresa; José, André Cristiano; Monjane, Boaventura; Bidaurratzaga, Eduardo; Casimiro, Isabel; Trindade, João Carlos; Alberdi, Jokin; Cruz, Lucinda; Valle, Luísa de Pinho (Gernika Gogoratuz, 2020)
No final do seminário e das oficinas-grupos de trabalho procedeuse a um debate aberto para partilha das reflexões e identificação de conclusões principais: • A participação em espaços de consulta/decisão está muito condicionada pela falta de conhecimentos de quem participa, mas também pela falta de transparência e assimetria da informação. • A exclusão social está na base da pouca ou fraca participação e monitoria. • A qualidade da monitoria nos processos de governação e desenvolvimento é fraca. • A monitoria da governação e desenvolvimento é vista pelos poderes como «acções-sombra» ou «mandatados da oposição». • Os governantes têm medo de falar de desenvolvimento com a cidadania. Preferem discutir questões do partido. • Existem poucos espaços de participação criados e também reclamados. • Existe uma confusão de papéis e das suas compatibilidades entre as lideranças e a administração. • Não se aplica a lei, em muitos casos. • Existem lideranças reconhecidas e não reconhecidas. • Algumas iniciativas começam a ter os seus resultados na província, sobretudo no contexto urbano e relacionadas com grupos de jovens. • Algumas organizações da sociedade civil reproduzem dinâmicas de poder e definem o que é ou não prioritário para as comunidades (nos seus gabinetes). • Também existe corrupção e fraca prestação de contas entre as organizações da sociedade civil, não só na Administração/Governo. • Os jovens de Cabo Delgado necessitam ter formação e emprego nos grandes projectos de desenvolvimento.
978-84-09-17639-7
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; agriculture / agricultura; conflict - civil war / conflito - guerra civil; conflict / conflito

Social asymmetries: clues to understand the spread of islamist jihadism in Cabo Delgado - Feijó, Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, João (Friedrich-Ebert-Stiftung Peace and Security, 2020)
This article intends to reflect around the level of poverty and inequality existing among the various ethno-linguistic groups of the province, trying to gauge the extent to which they may be at the root of the current conflict. In this sense, 94 individuals were interviewed in the districts of Palma, Mocímboa da Praia, Macomia, Muidumbe and Montepuez (macuas, macondes, muânis and mácues), trying to understand what representations they build on the different ethno-linguistic groups in the province, in terms of access to business, employment and income, as well as State support. Throughout the text, an attempt is made to understand the socio-economic factors that can lead to the adherence (direct or indirect) of local populations to violent groups.
ISBN: 9782490093182 OCLC: 1199064112
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; conflict / conflito; poverty / pobreza

Face ao conflito no norte, o que pode Moçambique aprender com a sua própria guerra civil (1976-1992)? Uma análise das dinâmicas da insurgência em Cabo Delgago - Forquilha, Salvador; Pereira, João (Desafios para Moçambique 2020, 2020)
A história de Moçambique dos últimos 50 anos tem sido marcada por ciclos de violência armada de contestação ao Estado, não só colonial, como também pós-colonial. Com efeito, desde a guerra anticolonial levada a cabo pela Frente de Libertação de Moçambique (Frelimo), passando pela guerra civil, que opôs a Resistência Nacional Moçambicana (Renamo) ao Governo da Frelimo, até às crises político-militares pós-eleitorais, a violência armada tem estado presente no processo da construção do Estado em Moçambique. No início de Outubro de 2017, começou uma outra contestação violenta ao Estado na província de Cabo Delgado. No dia 5 de Outubro de 2017, um grupo de homens armados atacou as instituições do Estado na vila sede de Mocímboa da Praia. Inicialmente associado a um banditismo de mera perturbação da ordem pública, o fenómeno ganhou rapidamente proporções alarmantes. Os ataques começaram a multiplicar-se. Dois meses depois do primeiro ataque, a Polícia já havia detido 251 suspeitos, dos quais 37 eram cidadãos de nacionalidade tanzaniana (O País, 2017). Em Dezembro de 2017, a Polícia da República de Moçambique, ao mais alto nível, esteve na zona e visitou os distritos de Mocímboa da Praia e Palma. No comício popular que realizou na vila sede de Mocímboa da Praia, o Comandante Geral da Polícia, Bernardino Rafael, deu um «ultimato» aos atacantes de Mocímboa da Praia, decretando sete dias para se entregarem às autoridades (O País, 2017). No entanto, a violência continuou e, nas semanas e meses que se seguiram ao ataque à vila sede de Mocímboa da Praia, a situação de segurança piorou no terreno e os ataques espalharam-se para outros distritos da zona norte de Cabo Delgado. Entre finais de Março e meados de Abril de 2020, a violência armada atingiu níveis nunca vistos antes, com o assalto e a ocupação temporária de quatro vilas nos distritos de Mocímboa da Praia, Quissanga, Muidumbe e Ibo. Que factores estão na origem do avanço da insurgência no terreno? Que tipo de relação se vai desenvolvendo entre os insurgentes e as populações locais? Existe algum potencial para que a insurgência se alastre para o Sul, em direcção à zona costeira de Nampula? Como tem vindo o Estado a responder à insurgência? Estas perguntas são uma parte importante do programa de pesquisa intitulado «Estado, violência e desafios de desenvolvimento no Norte de Moçambique», em curso no IESE desde Agosto de 2019.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict - civil war / conflito - guerra civil; conflict - violent extremism / conflito - extremismo violento; conflict / conflito

Mozambique: Military maritime cooperation agreement with France under discussion - Lusa (Club of Mozambique, 2020)
Mozambique and France are discussing a military maritime cooperation agreement, a diplomatic source in the European country told Lusa in the context of possible support in the fight against terrorism in Cabo Delgado. "No operational military support has been provided to Cabo Delgado by the French
Keywords: #Reporting & Media / Reportagem & Mídia; *tagged; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; GP - Cabo Delgado; L - english / inglês; conflict / conflito

Cabo Delgado e o Risco Sistémico da Guerra em Moçambique - Ngoenha, Severino; do Amaral, Giverage; Nhumaio, Alcido (Desafios para Moçambique 2020, 2020)
Em Moçambique a guerra é um risco sistémico: na linguagem de Thomas Hobbes, é a mãe de todos os riscos. A guerra é transversal a todos os outros riscos em termos de consequências sociais, económicas, políticas e culturais: destrói as infra-estruturas, como a rede escolar, os hospitais, as vias de acesso e os tecidos sociais; enfraquece a economia; paralisa a agricultura; apodera-se da indústria; e instala a fome, a miséria e toda a espécie de desgraças. A guerra é o maior dos riscos sistémicos de Moçambique não apenas pelos seus efeitos altamente destrutivos, mas porque agrava a probabilidade de ocorrência dos demais riscos aos quais o País está sistemática e concomitantemente exposto. Em geral, as considerações sobre a guerra em Moçambique são feitas de duas maneiras diferentes. De um lado, a abordagem político-militar, que privilegia a busca de mecanismos de diálogo entre os beligerantes, o que supõe o conhecimento e o reconhecimento entre as partes e das razões que levam uns e outros a optar por um confronto armado. Esta abordagem tem sido a adoptada pelos diferentes governos moçambicanos que enfrentaram conflitos nos seus mandatos, ou seja, todos. Actualmente não parece que uma tal via se vislumbre salutar nas estratégias contra os dois conflitos armados em curso no Centro e Norte do País. Por outo lado, a abordagem técnico-científica, que parte do pressuposto de que o fenómeno da guerra é complexo e privilegia uma epistemologia interdisciplinar, na qual participam muitos saberes disciplinares no esforço de apreender as suas razões e causas. Esta abordagem procura entender o que leva o País a fazer da guerra o seu modus vivendi, o que leva grupos, partidos e facções militares a optarem sistematicamente pela confrontação militar.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

O Cabo do Medo - O Daesh em Moçambique 2019-2020 - Rogeiro, Nuno (UCCLA, 2020)
Toda a verdade sobre a situação explosiva do domínio do Norte de Moçambique pelo Daesh. É o primeiro livro a nível mundial que revela em primeira mão o que se está a passar na zona de Cabo Delgado: a conquista e subjugação das populações, a violência bárbara com recurso a decapitações e execuções sumárias, a exploração das pessoas e dos recursos disponíveis, a impotência das autoridades moçambicanas em impor a ordem e a paz social. Um livro de grande acualidade que desvenda uma realidade tão chocante quanto desconhecida. “Uma análise exaustiva da ocupação desta terra boa (nordeste de Moçambique), de gente boa, pelo Daesh. Tem de ser combatido mas, primeiro, tem de ser compreendido.” Nuno Rogeiro
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - portuguese / português; conflict / conflito

Vampiros, Jihadistas e Violência Estrutural em Moçambique: Reflexões sobre Manifestações Violentas de Descontentamento Local e as suas Implicações para a Construção da Paz - Weimer, Bernhard (Instituto de Estudos Sociais e Económicos (IESE), 2020)
Este ensaio, escrito em Março de 2018, procura explicar, numa perspectiva histórica, ataques violentos recentemente perpetrados contra instituições locais e representantes do Estado moçambicano. São usados estudos de caso de três províncias moçambicanas, aos quais se acrescentam casos históricos de ataques armados com padrões e alvos semelhantes. Com base em investigação documental, entrevistas e análise da literatura de Antropologia e Economia Política, são identificadas três causas principais dos conflitos locais – todos eles com os seus contextos e narrativas específicos: em primeiro lugar, a economia política com raízes históricas, dominada pela Frelimo, lida com o descontentamento e a divergência de forma autoritária e muitas vezes violenta, ou, nas palavras do antropólogo Bjørn Bertelsen, com «guerra como governação»; Em segundo lugar, a Ordem de Acesso Limitado firmemente estabelecida em Moçambique produz a exclusão socioeconómica de intervenientes e interesses sociais, económicos e políticos locais, nomeadamente quando se relaciona com extracção de recursos naturais; e um terceiro factor é uma perspectiva de que «não há futuro» da juventude moçambicana, a maioria demográfica. Presa numa idade da espera (waithood, Alcinda Honwana), esta juventude está alienada das suas comunidades e culturas locais, mas não foi absorvida pela sociedade e pela economia. Isso torna os jovens do sexo masculino vulneráveis a influências globais e às promessas dos seus pares, às vezes relacionados com redes de pensamento religioso radical e de criminalidade. O ensaio analisa também a medida em que a parte nordeste de Moçambique, com os seus enormes investimentos numa indústria de Gás Natural Liquefeito (GNL), é vulnerável à influência do islamismo militante. O estudo termina com sugestões para enfrentar os conflitos locais, que surgem numa altura em que a «guerra» de longa data entre o Governo da Frelimo e a Renamo está a ser negociada visando um acordo político.
978-989-8464-46-0
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; GP - Nampula; GP - Niassa; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; governance / governação; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Walking the talk?: A critical perspective on sustainable peace and reconciliation in Mozambique - Weimer, Bernhard (Friedrich-Ebert-Stiftung, Peace and Security Centre of Competence Sub-Saharan Africa, 2020)
The August 2019 Maputo Accord on Peace and Reconciliation appears not to be standing on entirely solid ground. Not only has the decentralization agreement suffered from last minute ‘adulteration’, but also the DDR process has been lacking speed and rigour. The circumstances and outcomes of the October 2019 elections have cast doubt on the extent to which Renamo will abide to the August 2019 agreement. The party appears to be split on the matter of the – officially disowned armed Junta Militar maintaining low-intensity, nevertheless deadly, attacks on civilian traffic in central Mozambique. Thus it remains doubtful at the beginning of 2020 to what extent the ambitious DDR process, the key Pillar/Provision of the most recent peace agreement, may be implemented and by when. Further, the institutional setup of the Peace Secretariat and the donor-financed MDTF for DDR process leave doubts about national ownership of and responsibility for the implementation of the Peace Agreement, which uses reconciliation as a token, but avoids getting to its substance. Apart from these factors, the summary amnesty legislation benefitting both former warring parties prevents the possibility of publicly discussing justice and pursuing war crimes. With Frelimo’s impressive, albeit amply contested, win of the 2019 elections at the national level and provincial tier of government, the paradigm of ‘winner takes all’ may come back into political reality, which in the past had triggered armed conflict and prompted political negotiations on some degree of power sharing through decentralization arrangements. In some senior political circles, this paradigm is now paraphrased as the introduction of a benevolent authoritarian African regime, at the cost of democratic checks and balances and a strong civil society. Under these circumstances, reconciliation initiatives as sketched above , primarily promoted by civil society in the broadest sense and including FBOs, would seem a viable strategy to breathe new life into the August 2019 agreement and opening space for the youth to actively engage the political parties which, up to today, they had talked peace but remained prepared for war. Only Chissano, in the aftermath of the Rome General Peace Accord, attempted to ‘walk the reconciliation talk’. The present constellation and the terrible consequences for lives and livelihoods in Cabo Delgado would also represent a strategic opportunity to become actively involved in peace consolidation, from which the Mozambican CSOs have been kept at a distance, leaving peace-making to political leaders only. A Malawian proverb suggests that he who thinks he is leading but has no followers is only taking a walk.
OCLC: 1164631287
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; conflict - civil war / conflito - guerra civil; conflict / conflito

Paz e Reconciliação em Moçambique: conjunturas críticas e dependência da trajectória - Weimer, Bernhard; Bueno, Natália (Desafios para Moçambique 2020, 2020)
Com base em estudos anteriores (Bueno, 2017; 2019; Weimer, 2020), recorremos aos conceitos de dependência da trajectória (em inglês, path dependence) e conjunturas críticas (em inglês, critical junctures) como duas lógicas explicativas para construir a nossa análise. Como se explica mais adiante, estas lógicas são muito usadas em análises históricas. Revisitamos, assim, o caso de Moçambique e examinamos o desenvolvimento da reconciliação, dando maior prioridade ao acordo de paz assinado em Agosto de 2019. Defendemos que, por muito que estes acordos de paz se inscrevam em contextos mais amplos de conjunturas críticas para a construção da paz, democratização e descentralização, as leis de amnistia a eles ligados podem inscrever-se numa lógica de dependência da trajectória. Na segunda secção do artigo, ocupamo-nos, primeiro, da literatura sobre conjunturas críticas, dependência da trajectória, reconciliação e amnistia para apresentar os principais debates sobre os conceitos usados neste estudo, bem como para definir o potencial explicativo que resulta da inter-relação entre esses elementos. Deste exercício resulta a chamada «abordagem contabilística», que, depois, aplicamos ao caso de Moçambique na terceira secção, que é dedicada à análise da reconciliação no País, examinando sobretudo o seu desenvolvimento no contexto do Acordo de Paz e Reconciliação de Maputo. Finalmente, na última secção, sintetizamos o argumento, apresentamos algumas observações finais e fazemos algumas recomendações políticas assentes na literatura e nas melhores práticas internacionais
Keywords: *indexed; G - Mozambique / Moçambique; L - portuguese / português; conflict - civil war / conflito - guerra civil